NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Signal detection of ferric carboxymaltose-induced serious adverse events: disproportionality analysis of FAERS and VigiBase data and systematic review of case reports - Reddikumar Reddy Galigutta; Christy Thomas; Mahesh Rathod; P. N. Hasik; R. S. Ray; Jai Prakash; Krishna Undela (European Journal of Clinical Pharmacology, 2025)

Fruit waste-derived cellulose-polyaniline composite for adsorption-coupled reduction of chromium oxyanions - Pratiksha Joshi; Sweta Mehta; Ramesh N. Goswami; Manoj Srivastava; Anjan Ray; Om P. Khatri (Environmental Science and Pollution Research, 2024)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Sustainable Growing Areas for Sugarcane in Sri Lanka Under a Changing Climate - D. M. B. M. Deegala; N. S. Abeysingha; L. P. Muthuwatta; Ram L. Ray (Sugar Tech, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A review of regulations and guidelines related to winter manure application - Jian Liu; Peter J. A. Kleinman; Helena Aronsson; Don Flaten; Richard W. McDowell; Marianne Bechmann; Douglas B. Beegle; Timothy P. Robinson; Ray B. Bryant; Hongbin Liu; Andrew N. Sharpley; Tamie L. Veith (Ambio, 2018)

Ecology of Endomycorrhizal Association in Musa spp. of South India - K. S. Nidheesh; N. Valsalakumar; V. P. Potty; J. G. Ray (Symbiosis, 2018)

Nano silver-embedded electrospun nanofiber of poly(4-chloro-3-methylphenyl methacrylate): use as water sanitizer - Mehdihasan I. Shekh; Nirmal N. Patel; Kaushal P. Patel; Rajnikant M. Patel; Arabinda Ray (Environmental Science and Pollution Research, 2017)

Effects of biological, economic and management factors on tuna and billfish stock status - Maite Pons; Trevor A Branch; Michael C Melnychuk; Olaf P Jensen; Jon Brodziak; Jean M Fromentin; Shelton J Harley; Alan C Haynie; Laurie T Kell; Mark N Maunder; Ana M Parma; Victor R Restrepo; et al. (Fish and Fisheries, 2017)
Commercial tunas and billfishes (swordfish, marlins and sailfish) provide considerable catches and income in both developed and developing countries. These stocks vary in status from lightly exploited to rebuilding to severely depleted. Previous studies suggested that this variability could result from differences in life‐history characteristics and economic incentives, but differences in exploitation histories and management measures also have a strong effect on current stock status. Although the status (biomass and fishing mortality rate) of major tuna and billfish stocks is well documented, the effect of these diverse factors on current stock status and the effect of management measures in rebuilding stocks have not been analysed at the global level. Here, we show that, particularly for tunas, stocks were more depleted if they had high commercial value, were long‐lived species, had small pre‐fishing biomass and were subject to intense fishing pressure for a long time. In addition, implementing and enforcing total allowable catches ( TAC s) had the strongest positive influence on rebuilding overfished tuna and billfish stocks. Other control rules such as minimum size regulations or seasonal closures were also important in reducing fishing pressure, but stocks under TAC implementations showed the fastest increase of biomass. Lessons learned from this study can be applied in managing large industrial fisheries around the world. In particular, tuna regional fisheries management organizations should consider the relative effectiveness of management measures observed in this study for rebuilding depleted large pelagic stocks.

The energy‐conserving electron transfer system used by D esulfovibrio alaskensis strain G 20 during pyruvate fermentation involves reduction of endogenously formed fumarate and cytoplasmic and membrane‐bound complexes, Hdr‐Flox and Rnf - Birte Meyer; Jennifer V. Kuehl; Morgan N. Price; Jayashree Ray; Adam M. Deutschbauer; Adam P. Arkin; David A. Stahl (Environmental Microbiology, 2014)
Summary The adaptation capability of D esulfovibrio to natural fluctuations in electron acceptor availability was evaluated by studying D esulfovibrio alaskensis strain G 20 under varying respiratory, fermentative and methanogenic coculture conditions in chemostats. Transition from lactate to pyruvate in coculture resulted in a dramatic shift in the population structure and closer interspecies cell‐to‐cell interactions. Lower methane production rates in coculture than predicted from pyruvate input was attributed to redirection of electron flow to fumarate reduction. Without a methanogenic partner, accumulation of H 2 and formate resulted in greater succinate production. Comparative transcript and gene fitness analysis in concert with physiological data of G 20 wildtype and mutants demonstrated that pyruvate fermentation involves respiration of cytoplasmically formed fumarate using cytoplasmic and membrane‐bound energy‐conserving complexes, Rnf , Hdr‐Flox ‐1 and Hmc. At the low H 2 /formate levels maintained in coculture, Rnf likely functions as proton‐pumping ferredoxin (Fd) : type‐I cytochrome c oxidoreductase, which transitions to a proton‐pumping Fd red : nicotinamide adenine dinucleotide ( NAD + ) oxidoreductase at high H 2 /formate levels during fermentation in monoculture. Hdr‐Flox ‐1 is postulated to recycle Fd red via a flavin‐based electron bifurcation involving NADH , Fd ox and the thiol/disulphide‐containing DsrC . In a menaquinone ( MQ )‐based electron confurcation reaction, the high‐molecular‐weight cytochrome‐c 3 complex, Hmc , is proposed to then couple DsrC red and periplasmic H 2 /formate oxidation using the MQ pool to fuel a membrane‐bound fumarate reductase.

Trends in seasonal temperatures over the Indian region - Nilesh K Wagholikar; K C Sinha Ray; P N Sen; P Pradeep Kumar (Journal of Earth System Science, 2014)

Targeting oncogenic ALK and MET: a promising therapeutic strategy for glioblastoma - Gerald C. Wallace; Yaenette N. Dixon-Mah; W. Alex Vandergrift; Swapan K. Ray; Catherine P. Haar; Amber M. Mittendorf; Sunil J. Patel; Naren L. Banik; Pierre Giglio; Arabinda Das (Metabolic Brain Disease, 2013)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Bromus catharticus striate mosaic virus: a new mastrevirus infecting Bromus catharticus from Australia - James Hadfield; Darren P. Martin; Daisy Stainton; Simona Kraberger; Betty E. Owor; Dionne N. Shepherd; Francisco Lakay; Peter G. Markham; Ray S. Greber; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2011)

Assessment of the Jason-2 Extension to the TOPEX/Poseidon, Jason-1 Sea-Surface Height Time Series for Global Mean Sea Level Monitoring - B. D. Beckley; N. P. Zelensky; S. A. Holmes; F. G. Lemoine; R. D. Ray; G. T. Mitchum; S. D. Desai; S. T. Brown (Marine Geodesy, 2010)

Shift in detrital sedimentation in the eastern Bay of Bengal during the late Quaternary - C. Prakash Babu; J. N. Pattan; K. Dutta; N. Basavaiah; G. V. Ravi Prasad; D. K. Ray; P. Govil (Journal of Earth System Science, 2010)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Trace element geochemistry of Amba Dongar carbonatite complex, India: Evidence for fractional crystallization and silicate-carbonate melt immiscibility - Jyotiranjan S. Ray; P. N. Shukla (Journal of Earth System Science, 2004)

DDT and HCH Residues in Basmati Rice (Oryza sativa) Cultivated in Dehradun (India) - G. Suresh Babu; M. Farooq; R. S. Ray; P. C. Joshi; P. N. Viswanathan; R. K. Hans (Water, Air, & Soil Pollution, 2003)

High iridium concentration of alkaline rocks of Deccan and implications to K/T boundary - P. N. Shukla; N. Bhandari; Anirban Das; A. D. Shukla; J. S. Ray (Journal of Earth System Science, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Rabies viruses infect primary cultures of murine, feline, and human microglia and astrocytes - N. B. Ray; C. Power; W. P. Lynch; L. C. Ewalt; D. L. Lodmell (Archives of Virology, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)